Factores críticos para la perdurabilidad y el continuo desarrollo de mipymes pertenecientes a la industria gastronómica de Bogotá D.C. (2021)
This research is made with the purpose of identify critical success factors for perdurability and constant development of Bogota`s gastronomic industry SMEs after COVID-19 pandemic in 2020. By Inquiring aspects like apprenticeship, culture, government and strategic. Trough the comparision between teoric information and data from 63 experienced enterprises (more tan a year of existence).